THE IMPACT OF WORKLOAD, REWARD AND WORK ENVIRONMENT ON EMPLOYEES PRODUCTIVITY OF UD. RODAMAS - David A. Worotikan; Willem J. F. A. Tumbuan; Fitty V. Arie (Universitas Sam Ratulangi, 2023)
Employee productivity is an important aspect in ensuring every business‘s continuity. Workload, reward and work environment are three factors that are significant in the understanding, maintaining and boosting employees ‘productivity from any company or business unit. This study aims to figure out the influence of workload, reward and work environment to employees ‘productivity on UD. Rodamas employees. Overall population in this research is all employees of UD. Rodamas and the chosen sample is 30 respondents. Data analysis uses multiple linear regressions analysis method. This research result proves that workload and reward simultaneously and partially have positive and significant influence employees ‘productivity on UD. Rodamas employees and only work environment that give the positive and insignificant impact. Its management have to preserve and boost workload, reward and work environment in this company and deliberate other factors that influence the employees ‘productivity on UD. Rodamas employees. Keywords: workload, reward, work environment, employee productivity